Time slotted channel hopping with collision avoidance. (2018) - Hammoudi, Sarra; Harous, Saad; Aliouat, Zibouda; Louail, Lemia
Time slotted channel hopping (TSCH) mode proposed by the IEEE 802.15.4e-2015 standard enhances the reliability of low-power networks. TSCH supports the critical applications embedded in harsh environments with high-efficiency. Multi-channel hopping and time slotted access nature of this mode provides deterministic latency for applications and achieves a greater throughput capacity. The shared links nature of this mode risks the packets transmission to fail when the participating nodes are colliding nodes. Retransmitting the packets randomly risks it to fail several times, influencing the sensor energy and packet latency. To ensure collision avoidance in the presence of hidden nodes, we provide: time slotted channel hopping with correct collision avoidance backoff algorithm (TSCH-CCA) and Enhanced priority channel access backoff algorithm (E-PCA)) applied respectively to both normal packets and critical events packets. Our solution shows significant improvements in terms of latency, network congestion, network lifetime, critical event packets lifetime, and collision avoidance.